MINAT ORANG TUA MENYEKOLAHKAN ANAK PADA LEMBAGA PAUD MIFTAHUSSALAM DI DESA LAMBANGKUNING KECAMATAN LUMBANG PROBOLINGGO - Murtin; Robiatul Adawiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe parents’ interest in enrolling their children at the Early Childhood Education (PAUD) institution Miftahussalam in Lambangkuning Village, Lumbang District, Probolinggo Regency, as well as to identify the supporting and inhibiting factors that influence their decisions. The research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving the school principal, teachers, and selected parents, using purposive sampling techniques. Data analysis was conducted using the interactive model of Miles and Huberman, which consists of three stages: data reduction, data display, and conclusion drawing or verification. Data validity was ensured through source and technique triangulation. The findings indicate that parents’ interest in enrolling their children at PAUD Miftahussalam is driven by several supporting factors, including the competence and caring nature of the teachers, an Islamic, safe, and enjoyable school environment, affordable tuition fees, support from community and religious leaders, and age-appropriate learning programs. Meanwhile, inhibiting factors include the community’s low awareness of the importance of early childhood education, families’ limited economic capacity, and geographical barriers as well as transportation constraints. This study concludes that parents’ interest in early childhood education is shaped by the interaction between internal and external factors, such as perceptions of the benefits of education, social support, and economic and environmental conditions. The results are expected to serve as a reference for educational institutions and policymakers in formulating strategies to enhance community participation in early childhood education, particularly in rural areas